1983
DOI: 10.1002/omr.1270211002
|View full text |Cite
|
Sign up to set email alerts
|

Rotational equilibria in 1,2,6‐trisubstituted pyridinium cations and reactions of 2‐Isopropylpyrylium cations

Abstract: 2-Isopropyl-6-phenyl-and 2,6-diisopropyl-pyridiniums with bulky 1-substituents show temperature-variable NMR spectra which are interpreted in terms of restricted rotation. 2-Isopropyl-4,6-diphenylpyrylium can be deprotonated at the isopropyl group to give an anhydro base which forms new pyryliums with electrophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The 2,4,6-triphenyl Katritzky salt needed to deliver secondary benzylic sulfone 3ae was unstable. However, the 2-isopropyl analogue 1ae , previously reported by Katritzky, could be prepared and generated sulfone 3ae in 73% yield. Sulfinate salts could also be isolated; sodium sulfinates 2a – c could be obtained in excellent yields following simple acidification and extraction using aq.…”
mentioning
confidence: 86%
“…The 2,4,6-triphenyl Katritzky salt needed to deliver secondary benzylic sulfone 3ae was unstable. However, the 2-isopropyl analogue 1ae , previously reported by Katritzky, could be prepared and generated sulfone 3ae in 73% yield. Sulfinate salts could also be isolated; sodium sulfinates 2a – c could be obtained in excellent yields following simple acidification and extraction using aq.…”
mentioning
confidence: 86%
“…The possibility of flipping seems unlikely and could be completely ruled out by close packing considerations in the crystal and also due to unfavorable energetic requirements. The mechanism of C-C rotation appears to be more appropriate as the occurrences of such rotation in the gas and solution phases have been reported in the literature, [21][22][23][24][25][26][27] although it would contradict the report of Wang et al 28 claiming such solid state rotation as 'energetically forbidden'.…”
mentioning
confidence: 92%
“…While the C-C rotation phenomenon of several flexible groups such as the methyl, trifluoromethyl and tert-butyl groups in the solid state is well established, the behavior of the isopropyl group is still under debate. There are a few papers reporting the rotation of the isopropyl group in gas and solution phases observed by NMR and other spectroscopic techniques; [21][22][23][24][25][26][27] however, to the best of our knowledge, no single report to date claims to have observed isopropyl rotation in the solid state. Moreover, recent experimental and theoretical studies on 3-isopropylchrysene carried out by Wang et al rule out the feasibility of the rotation of the isopropyl group in the solid state.…”
mentioning
confidence: 99%
“…For example, in 2,4,6-trimethyl pyrylium, it was observed that both the 2/6-methyl (α) and 4-methyl (γ) hydrogens exchanged with D 2 O, with the latter being faster by 1 order of magnitude . This proceeds via the pseudobase intermediates (e.g., 4a and 4b ), which can be isolated sometimes. , Detailed studies carried out by Williams on the hydrolysis of pyryliums found that the p K a of 2,4,6-trimethylpyrylium ion acting as a carbon acid in water was 6.7.…”
Section: Introductionmentioning
confidence: 99%
“…15 This proceeds via the pseudobase intermediates (e.g., 4a and 4b), which can be isolated sometimes. 1,16 Detailed studies carried out by Williams 17 on the hydrolysis of pyryliums found that the pK a of 2,4,6-trimethylpyrylium ion acting as a carbon acid in water was 6.7.…”
Section: ■ Introductionmentioning
confidence: 99%